OP0151-PARE WORK IMPACTS EXPERIENCED BY YOUNGER PEOPLE WITH ARTHRITIS: A SYSTEMATIC REVIEW. (2nd June 2020) - Berkovic, D.; Parker, C.; Ayton, D.; Briggs, A. M.; Ackerman, I.
Abstract : Background: On a global scale, it is estimated that adults in their peak income-earning years are disproportionately impacted by arthritis (1). Younger adults with arthritis are less likely to be employed and are more likely to face productivity challenges at work when compared to healthy similar-aged peers (2). The work-related impacts of arthritis on younger adults remain largely unexplored and are rarely considered in routine clinical care for arthritis. Objectives: To systematically identify, appraise and synthesise the available evidence on work impacts experienced by individuals aged 16-50 years with arthritis. Methods: Eligible studies from 2000 - 2020 were identified in OVID Medline, PsycINFO, Embase, and CINAHL databases using a comprehensive search strategy. Quantitative and qualitative studies containing self-reported data on the work impacts of arthritis on younger people were included. Quality assessment was undertaken using validated quality appraisal tools (3). Results: From a yield of 300 studies, 35 were included in the review. After quality assessment and exclusion of the lowest-ranked studies, 28 studies (17 quantitative, 11 qualitative) were analysed. Work outcomes data were organised into five themes (1-3 for quantitative outcomes, 4-5 for qualitative outcomes): (1) the impacts of arthritis on work productivity; (2) the impacts of arthritis on work participation; (3) other arthritis attributable workplace challenges; (4) barriers to work participation associated with arthritis, and (5) enablers to work participation associated with arthritis. For quantitative themes, arthritis was strongly associated with other workplace challenges: scores on the Workplace Activity Limitations Scale ranged from 5.9 (moderate workplace difficulty) to 9.8 (considerable workplace difficulty); and work disability relative to the healthy population (prevalence ranging from 6% - 80%). For qualitative themes, barriers to work participation included lack of workplace support; enablers included workplace support and intrinsic motivation to work. Conclusion: Arthritis is associated with poorer work outcomes for younger people relative to healthy peers. The available evidence was heterogeneous across studies. Additional research focusing solely on the unique workplace needs of younger population groups is required. This would inform the development of tailored intervention or workplace support strategies to maximise productive working years. References: [1]European League Against Rheumatism. Horizon 2020 Framework Programme: EULAR's positions and recommendations. EULAR 2011. [2]Jetha A. (2015). The impact of arthritis on the early employment experiences of young adults: A literature review. Disabil Health J. 8(3) 317-324. [3]Joanna Briggs Institute. Critical Appraisal Tools. The University of Adelaide 2019. Disclosure of Interests: None declared